Mixed-Reality Simulation to Support Practice Learning of Preservice Teachers - Sarah Gravett; Dean Van der Merwe; Sarita Ramsaroop; Pamela Tshabalala; Casey Bremner; Pumzile Mello (MDPI AG, 2023)
Before the COVID-19 pandemic, providing high-quality practice learning experiences for preservice teachers was already taxing due to the heavy reliance on school practicum, which is often besieged with challenges. Given these challenges, there is a growing urgency to explore alternative avenues for offering practice learning experiences to preservice teachers in addition to school practicum. With this backdrop, a qualitative study was conducted, employing observation and interviews as data collection methods to explore the potential of mixed-reality simulation (MRS) to strengthen the practice learning experiences of preservice teachers. The core teaching practice of questioning was chosen to explore the affordances of MRS for improving preservice teachers' understanding of and proficiency in utilizing questioning. This study found that MRS provides a low-risk learning environment that preservice teachers perceive as authentic. For these reasons, this environment is conducive to improvement, and it enables deliberate practice, which is vital for nurturing metacognition and adaptive expertise. The findings also highlight the importance of coaching for maximizing MRS advantages. The absence of coaching will most likely limit the affordances of MRS as an approximation of teaching practice. While our findings are promising, the resource-intensive nature of MRS implementation means that scalability requires further investigation.